Discovering Factors that Influence the Use of Augmented Reality for Communication on Active Highway Construction Sites. Issue 5 (May 2023) - Kassis, Rita El; Ayer, Steven K.; Asmar, Mounir El; Tang, Pingbo
The construction industry requires effective communication between project stakeholders in various locations. This communication can be facilitated by in-person site visits or phone calls. However, these methods can lead to wasted travel time or the omission of critical visual site details, respectively. In theory, augmented reality (AR) can support consistent understandings of site environments in a similar way to in-person visits but with the efficiency of phone calls. However, most studies exploring AR for communication in construction have done so in controlled environments. This work investigates the efficacy of AR calls in uncontrolled settings (i.e., active construction sites) by interviewing and recording practitioners who are using AR, to identify behaviors and perceptions that influence communication efficiency and effectiveness. The authors conducted qualitative analyses and identified 14 factors that can affect information exchanges between professionals using AR. The factors found in this study include: virtual manipulation; visual aids; shared action plan; hands-free operation; decision-making; site interaction; working remotely; repetition; locomotion; performing different job types; device discomfort; background noise; lighting conditions; and disconnection in hardware physical and feature components. Some factors represent beneficial opportunities for AR, while others pose challenges. Some of the identified challenges may be resolved through technological innovations and user training, as discussed in the paper. Furthermore, this work provides evidence of factors for which current AR technologies are sufficiently developed to guide near-term implementation in practice.